KOMPARASI PENDAPATAN PEDAGANG KAKI LIMA DI PASAR PULAU KIJANG DAN DI PASAR TANJUNG KABUPATEN INDARGIRI HILIR PROVINSI RIAU - Ramadhani, Anjelly; Antomi, Yudi (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to find out (1) Knowing the income of street vendors between the deer island market and the Cape market. (2) Knowing the factors affecting the income of street vendors, Kijang Island Market, and Tanjung Market. (3) Know the extent of the service of the deer island market with the Cape market. This type of research is comparative with a quantitative approach. The research data used multiple linear regression data analysis methods, independent T-test difference test, and buffering analysis. From the results of the study, it can be concluded that the independent t-test difference test has a comparison of PKL income in the antelope island market, it was found that the value of Sig. (2-tailed) was 0.042 < 0.05. The results of the multiple linear analysis methods show that the partial hypothesis test (t-test), simultaneous test (f-test), and coefficient of determination (R2) can be seen from the results of the determination coefficient test that the capital, working hours, and business location in the deer island market amounted to Fcalculate value 19,321 > Ftable 3.19 while the results of the coefficient determination test value in the cape market amounted to Fcalculate value 9,866 > Ftable 3.19. With a significant value in the deer island market and Cape market of 0.000 < (0.05). Data from the buffering analysis can be known by the range of services in the deer island market has a different radius. The Kijang island market can serve the reach of other regions, in contrast to the Cape market can not serve the reach of other regions. It can be concluded from the results of this study that the variables of capital, working hours, business location, and range of services can positively and significantly affect the income level of street vendors in the Kijang island market and the Cape market.